The Association of Parathyroid Hormone Related Protein and Vitamin D Level with Serum Calcium Ion in Acute Leukemia Patients - Niniek Wiendayanthi; MI. Diah Pramudianti; Yuwono Hadisuparto (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Acute leukemia is bone marrow clonal cell malignancy. One of its complications is hypercalcemia. Parathyroid Hormone-Related Protein (PTHrP) activities involve the regulation of Calcium (Ca) metabolism. Vitamin D is a steroid involved in Ca homeostasis and bone mineralization. This study aimed to analyze PTHrP and vitamin D levels with serum calcium ion in acute leukemia. A cross-sectional study was performed in Clinical Pathology Dr. Moewardi General Hospital Surakarta between July and August 2019, consisting of 41 subjects with new acute leukemia who were diagnosed based on bone marrow puncture and or immunophenotyping result. The cut-off value of Ca ion serum and PTHrP level were determined with a Receiver Operating Curve (ROC). The data were analyzed with a 2x2 table, followed by multivariate logistic regression analysis, and p<0.05 was considered significant. Statistical analysis showed the median age of 25 (2-68) years, 23 (56.10%) ALL, and 18 (43.90%) non-ALL patients. The median of Ca ion and PTHrP were 1.08 (0.84-1.21) mmol/l and 307.52 (20.77-1104.26) pg/mL, respectively. The mean level of vitamin D was 26.45±11.40 ng/mL. Bivariate analysis showed that PTHrP levels â‰¥ 110.09 pg/mL and vitamin D â‰¥ 20 ng/mL were related to serum Ca ion â‰¥ 1.07 mmol/l (PR 4.675; 95% CI: 1.211-18.041; p=0.021 and PR 5.143; 95% CI: 1.279-20.677; p=0.017). Multivariate analysis showed that PTHrP â‰¥ 110.09 pg/mL and vitamin D â‰¥ 20 ng/mL were associated with serum Ca ion â‰¥1.07 mmol/l. There was a significant association between PTHrP, vitamin D level, and serum Ca ion in acute leukemia patients.